(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3eHJhQ GdChd hChd GdehLhO efg CKfGA MQa GdUGO bhdg (B: (3GdehWC CHh bJGOI Cf GdfHi UdYe bGd (B:" (3EPG CbjeJ GdUdGI adG JbhehG MJi JQhfi bO NQLJ , hYdjce HGdScjfI(B" (3CNQLg GdLeGYI EdG GdehWC s
(3BNQgG (B:s
(3eHJhQ GdBNQ hBNQ GdehLhO efg CKfGA MQa GdbGa bhdg (B: (3abGd HGQc Gddg dc ajgG , bGd aCJi GdCbQY abGd Ci TF CMH Edjc s
(3GdLRA GdKGfi ef fSNI CNQi (B,s
(3HMhGTjgG JYdjbGJs
(3GdfSNI HgG MhGTs
(3hcJHJ GdYfGhjf HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3GdMOjK h GdeUWdMs